2021
DOI: 10.3389/fcell.2021.711815
|View full text |Cite
|
Sign up to set email alerts
|

Effect, Mechanism, and Applications of Coding/Non-coding RNA m6A Modification in Tumor Microenvironment

Abstract: The tumor microenvironment (TME), which includes immune cells, fibroblasts, and other components, is the site of tumor cell growth and metastasis and significantly impacts tumor development. Among them, N6-methyladenosine RNA modifications (m6A RNA modifications) are the most abundant internal modifications in coding and non-coding RNAs, which can significantly influence the cancer process and have potential as biomarkers and potential therapeutic targets for tumor therapy. This manuscript reviews the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 157 publications
(161 reference statements)
0
12
0
Order By: Relevance
“…Its expression directly affects the proliferation, invasion, and migration of tumor cells while enhancing the activity of immune cells and giving them an advantage [ 77 ]. Secondly, the tumor microenvironment serves as the site of tumor cell genesis and development, so improving the tumor microenvironment will affect the progression of tumor development [ 78 , 79 ]. Cytoskeleton protein 4.1 is a tumor metastasis suppressor, and there are multiple ways to restore or promote cytoskeleton protein 4.1 expression, including targeting partners that interact with cytoskeleton protein 4.1 [ 46 ].…”
Section: Clinical Application Of Cytoskeleton Protein 41 In the Tumor...mentioning
confidence: 99%
“…Its expression directly affects the proliferation, invasion, and migration of tumor cells while enhancing the activity of immune cells and giving them an advantage [ 77 ]. Secondly, the tumor microenvironment serves as the site of tumor cell genesis and development, so improving the tumor microenvironment will affect the progression of tumor development [ 78 , 79 ]. Cytoskeleton protein 4.1 is a tumor metastasis suppressor, and there are multiple ways to restore or promote cytoskeleton protein 4.1 expression, including targeting partners that interact with cytoskeleton protein 4.1 [ 46 ].…”
Section: Clinical Application Of Cytoskeleton Protein 41 In the Tumor...mentioning
confidence: 99%
“…Non-coding RNAs are dysregulated in tumor cells as well as stromal cells which provides a novel perspective for the regulation of TME components ( Di Agostino et al, 2022 ). Moreover, studies have shown that RNA N6-methyladenosine (m6A) modification plays a substantial role in TME diversity and complexity ( Li et al, 2021 ; Si et al, 2021 ).…”
Section: Non-coding Rna and Cancer Developmentmentioning
confidence: 99%
“…m6A RNA modifications are reversible epigenetic RNA modifications that modulate splicing, degradation, and other biological processes of RNAs. m6A RNA modifications of non-coding RNA are associated with tumorigenesis, metastasis, and other tumor characteristics ( Li et al, 2021 ; Si et al, 2021 ). Specifically, Jing et al summarized the biological function, mechanism, and clinical significance of m6A RNA modifications in head and neck squamous cell carcinoma (HNSCC) from a systematic perspective.…”
Section: Non-coding Rna and Cancer Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…m 6 A plays critical roles in both the innate and adaptive immune responses and in tumor immunology, which provides important hints for developing various types of antitumor immunotherapies ( 22 , 31 ). m 6 A also plays a vital role in the complex regulatory network within the TIME, and subsequently affects tumor occurrence, progression, metastasis, and treatment response ( 39 42 ). Most of the anticancer immune regulations rely on overcoming the continuous suppression of the adaptive immune response within the TME ( 43 ).…”
Section: A Modification As a Novel Regulator Of The Tumor Immune Microenvironmentmentioning
confidence: 99%